Implementasi Akad Murabahah pada Pembiayaan Kepemilikan Rumah Subsidi di BSI KCP Basuki Rahmat Situbondo - Zainol Hasan (Iltizam : Jurnal Ekonomi dan Keuangan Islam, 2024)
Indonesian Sharia banks have an important role in society because their activities refer to Islamic law. One of the existing products was the BSI Griya Hasanah product using a murabahah (sale and purchase) contract to make it easy for people (customers) to own their dream home. The method in this research used field research and the approach used was qualitative. The results of this research showed that the murabahah contract used at BSI KCP Basuki Rahmat Situbondo has several stages, namely: BSI and the customer enter into a usury-free murabahah contract, the goods being bought and sold were not prohibited by Islamic sharia. In addition, BSI finances part or all of the purchase price of goods whose qualifications have been agreed upon and BSI purchases goods required by customers on behalf of BSI. Apart from that, BSI conveys all matters relating to purchasing and then selling the goods to customers, customers fill out the agreement and pay the instalments.